Locational flexibility of the manufacturing multinational enterprise: a framework and two case studies - Lucas Van Wunnik (European Regional Science Association (ERSA), 2011)
In this paper, I try to develop a framework, which presents the factors influencing the mobility capacity of the manufacturing activity of a multinational enterprise (the difficulty/ease with which it can transfer its manufacturing activity from the initial host territory to another territory). I differentiate five factors: (1) the nature (generic vs. specific) of the territorial resources used by the multinational's subsidiary; (2) market access offered by production in the host territory; (3) the durability and specificity of the fixed assets owned by the multinational enterprise in the host territory; (4) other barriers making exit out of the host territory difficult (redundancy costs, interrelatedness of the subsidiary's activity with other units of the multinational enterprise, etc.); and (5) the availability of substitute plants by the multinational enterprise that can take over the production of the host territory's subsidiary. Once the framework is presented, I use it to analyse the mobility potential of the activities of two multinational enterprises: a Taiwanese company (Nien Hsing Textile Co.) that was assembling trousers in Nicaragua (fieldwork in 1998 and 2007) and a Japanese company (Sony) that was assembling television sets and manufacturing cathode ray tubes in Wales (fieldwork in 2000-2001). The study shows the importance, in the short run, of the heaviness of the capital goods used in production as factor limiting mobility. In the long run, however, the degree of specificity (uniqueness) of the territorial resources employed by the multinational enterprise (qualified labour, specialised suppliers, etc.) is crucial. The study shows also the risk of the "no-upgrading trap" of inward manufacturing investment for peripheral host territories. Indeed, multinational enterprises that realise small profit margin activities, and in which labour costs occupy an important share in total production costs, will want to maintain their international mobility capacity to be able to respond swiftly to changes in the configuration of location advantages. Therefore, they will restrict their sunk investments (in fixed assets, in training, in collaborations with local suppliers, etc.) in the host territory. This strategy counters the local embeddedness of the subsidiary and limits its structural economic impact on the host territory.
Keywords: 330